From the sources of normativity to metaeguical constructivism in Christine Korsgaard: Das fontes da normatividade ao construtivismo metaético em Christine Korsgaard - Moura, Andrew (Sofia, 2026)
By raising the “normative question”, Christine Korsgaard inquiries about the possibility of justification in practical philosophy. We shall try to clear up what is implied in that question and try to recognize in which aspects some traditional answers to it are incorporated by the philosopher. From there on it’ll follow the constitutivist thesis about agency and its consequences to the Kantian (and procedural in nature) enterprise of Korsgaard. A strain of metaethical constructivism results from this fundamental structure, in which practical normativity in general is constituted by beings who take themselves to be valuable and are uniquely capable of evaluating considerations qua reasons. As a conclusion, we shall make use of different cotemporary ways of understanding the constructivist position in general to interpret Korsgaard’s position in regard to this aspect as a way of making this philosophical strain within metaethics clearer.
Keywords: constructivism; constitutivism; metaethics; normativity; practical reason